POLA PENYELESAIAN KONFLIK: STUDI KASUS PEMETAAN WILAYAH ADAT PAPUA PEGUNUNGAN - sabriani sabriani; Andi Astri Faradiba; Yusman Yusman (Jurnal Honai, 2024)
The pattern of approaches to resolving social conflicts in Papua requires a deep understanding of the cultural, political and historical context of the region. Several patterns of approach that might be used in resolving the conflict in Papua include various things. Holding open dialogue between the government, community groups and local (customary) leaders, mediation, establishing community forums, and providing greater access to human resources in expressing opinions on the conflicts they face, this can reduce social tension because According to indigenous peoples, recognizing and respecting cultural diversity and ethnic identity in Papua is a great honor. The focus of this research is to find out the patterns of problem solving carried out by indigenous communities, especially the indigenous communities of Mountain Papua. A holistic approach by studying books, journals, events exposed on social media, previous and ongoing research that will be used as data to solve this problem. The patterns found combining these various elements are likely to be more effective in dealing with social conflict in Highland Papua and promoting peace and sustainable development in the region.